Variations in Root Canal Morphology of Mandibular Incisors in a North Indian SubPopulation: A Retrospective Cone-Beam Computed Tomography Analysis - Brar Prabhleen Kaur; Brar Rajdeep; Vashisht Ruchi; Mehta Nishant; Shrivastava Richa; Tamchos Rigzin (Wolters Kluwer Medknow Publications, 2024)
Background: There is a high failure rate of endodontic treatment in the mandibular incisors due to insufficient knowledge of the morphology. Aim: The aim of this study was to analyze the root canal morphology in mandibular incisor teeth in the North Indian subpopulation to improve the outcome of endodontic treatment. Setting and Design: A cross-sectional study was conducted at the OPD of a tertiary care institute. Materials and Methods: A total of 200 mandibular central incisors and 200 mandibular lateral incisors were selected from available cone-beam computed tomography examinations of 100 patients aged 18-79 years. They were evaluated for root canal system configuration and symmetry between right and left elements in the same individual. Statistical Analysis: Chi-square/Fisher's exact test was used to find the association between different study variables. Results: For mandibular central incisors, type I Vertucci classification was present in 69% of cases, type II in 3.5%, type III in 18.5%, type IV in 2%, and type V in 7% of cases. For mandibular lateral incisors, type I was present in 70.5% of cases, type II in 4% of cases, type III in 19.5%, type IV in 2%, and type V in 4% of cases. There was no evidence of types VI, VII, and VIII. Symmetry of root canal morphology between left and right teeth was observed in 90% of central incisors and 93% of lateral incisors. Conclusion: Type I Vertucci configuration was the most prevalent; however, the prevalence of other configurations is also evident. Therefore, endodontists should explore the morphology of these teeth carefully while performing root canal treatments.